Bioinspired Hydrogel Interferometer for Adaptive Coloration and Chemical Sensing. Issue 21 (11th April 2018) - Qin, Meng; Sun, Mo; Bai, Ruobing; Mao, Yiqi; Qian, Xiaoshi; Sikka, Dipika; Zhao, Yuan; Qi, Hang Jerry; Suo, Zhigang; He, Ximin
Abstract: Living organisms ubiquitously display colors that adapt to environmental changes, relying on the soft layer of cells or proteins. Adoption of soft materials into an artificial adaptive color system has promoted the development of material systems for environmental and health monitoring, anti‐counterfeiting, and stealth technologies. Here, a hydrogel interferometer based on a single hydrogel thin film covalently bonded to a reflective substrate is reported as a simple and universal adaptive color platform. Similar to the cell or protein soft layer of color‐changing animals, the soft hydrogel layer rapidly changes its thickness in response to external stimuli, resulting in instant color change. Such interference colors provide a visual and quantifiable means of revealing rich environmental metrics. Computational model is established and captures the key features of hydrogel stimuli‐responsive swelling, which elucidates the mechanism and design principle for the broad‐based platform. The single material–based platform has advantages of remarkable color uniformity, fast response, high robustness, and facile fabrication. Its versatility is demonstrated by diverse applications: a volatile‐vapor sensor with highly accurate quantitative detection, a colorimetric sensor array for multianalyte recognition, breath‐controlled information encryption, and a colorimetric humidity indicator. Portable and easy‐to‐use sensing systems are demonstrated with smartphone‐based colorimetric analysis. Abstract : A bioinspired hydrogel interferometer based on a single hydrogel thin film covalently bonded to a reflective substrate is reported as a simple and universal adaptive color platform. The single‐material‐based platform has advantages of remarkable color uniformity, fast response, high robustness, and facile fabrication, providing applications from chemical sensing to information encryption.